L’implant narratif (planting and payoff) au cinéma : une nécessité scénaristique ? - Toufic El-Khoury (Cahiers de Narratologie)
Planting/payoff is a narrative technique that favors the repeated use of an object or information during the story, a repetition which gradually acquires dramatic importance by helping to highlight key moments of the plot (moments of recognition, revelation or dramatic unveiling). A technique already used in novels, short stories, and theater, it is very popular in narrative film. While not specific to screenwriting, it nevertheless proves necessary in the construction of cinematic 'diegesis', as it responds to the principle of concentration specific to genres of dramatic imitation. It also allows for a symbiosis between the text and its potential visualization. Additionally, it participates in the mental construction of the story by explicitly calling upon the viewer's ability to grasp and apprehend the coherence of the story, connecting disparate elements to create, subjectively, a dramatic unity. Likewise, it proves to be an effective exercise for the screenwriter, testing their writing habits and renewing narrative conventions.